8x + 2y = 44
5x + 2y = 35
Since 2y is already common, there is no need for multiplication. Just reverse the signs on the equation.
Like this;
8x + 2y = 44
-5x - 2y = -35
All the additions become subtractions and vice versa.
-2y and +2y get cancelled.
Leaving;
8x = 44
-5x = -35
Now, subtract again.
8x - 5x = 3x
44 - 35 = 9
So;
3x = 9
x = 9 / 3
x = 3
We found 'x' and now we have to find 'y'.
Just substitute.
[8 x 3] + 2y = 44
24 + 2y = 44
2y = 44 - 24
2y = 20
y = 20 / 2
y = 10
Now, we re-check;
[8 x 3] + [2 x 10] = 44
24 + 20 = 44
Explaining the error for #9b is simply doing the whole sum.
Hope this helped! :) I tried my best to explain.
Answer:
13423
rtgffyygo 8.35 x 104 it should be that
G = 2
Hope This Is Sufficient !!
Answer:
7
Step-by-step explanation:
(-1^2)x 3 = 3
-1 x 4 = -4
3--4 = 7
Answer:
Step-by-step explanation:
a) is SAS (side , angle, side)
b) is SSA ( side , side angle) and also :P recognize you can't say (Angle Side, Side ) or the teacher will send you to the office for cussing :P